RANKL signaling in bone marrow mesenchymal stem cells negatively regulates osteoblastic bone formation. (December 2018) - Chen, Xiao; Zhi, Xin; Wang, Jun; Su, Jiacan
Abstract RANKL signaling is essential for osteoclastogenesis. Its role in osteoblastic differentiation and bone formation is unknown. Here we demonstrate that RANK is expressed at an early stage of bone marrow mesenchymal stem cells (BMSCs) during osteogenic differentiation in both mice and human and decreased rapidly. RANKL signaling inhibits osteogenesis by promoting β-catenin degradation and inhibiting its synthesis. In contrast, RANKL signaling has no significant effects on adipogenesis of BMSCs. Interestingly, conditional knockout ofrank in BMSCs withPrx1 -Cre mice leads to a higher bone mass and increased trabecular bone formation independent of osteoclasts. In addition, rank flox/flox :Prx1 -Cre mice show resistance to ovariectomy-(OVX) induced bone loss. Thus, our results reveal that RANKL signaling regulates both osteoclasts and osteoblasts by inhibition of osteogenic differentiation of BMSCs and promotion of osteoclastogenesis. Developmental Genetics: A dual-use gene regulates bone formation and breakdown Researchers in China have shown that a gene known for breaking bones down is also involved in making new bone. Bones are constantly repaired and reshaped by cells which break down bone tissue, osteoclasts, and those which create new bone, osteoblasts. The RANKL gene is known to play an important role in osteoclast development, but Jiacan Su of the Second Military Medical University has shown that it is also important for osteoblasts. Su's team detected high expression of RANKL and its receptor, RANK, in bone marrow stem cells, and the levels decreased as the stem cells differentiated into osteoblasts. Artificially increasing RANK expression decreased osteoblast differentiation, while reducing its expression increased osteoblast differentiation and bone mass. By showing that RANKL regulates osteoblasts as well as osteoclasts, these findings open new avenues for understanding bones development.